Spider communities from de Pacific region of the Valle del Cauca department, Colombia - FLÓREZ-D., EDUARDO (Revista Colombiana de Entomología, 2000)
The spider fauna was sampled in a tropical rain forest in the Reserva Natural de Escalerete, and the litoral zone near the locality of Ladrilleros, of the Department of Valle del Cauca (Southwest of Colombia), using diverse capture methods. It is registered the detected diversity [families and morphospecies], preference of microhabitats, efficiency of the capture methods, indexes of species richness, diversity and number of species estimated. The results obtained show a total of 482 specimens, grouped in 196 morphospecies, 26 families and two Suborders. The families with major diversity were Araneidae, Salticidae, Theridiidae, Tutragnathidae and Linyphidae. The preferred microhabitats were located in the arbustive and arboreal vegetation. The manual method, sweeping with entomological net and shak.ing the foliage, were the most effective for sampling the diversity of spiders.